2001
DOI: 10.1083/jcb.200105052
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cbfa1 in osteoblasts inhibits osteoblast maturation and causes osteopenia with multiple fractures

Abstract: Targeted disruption of core binding factor α1 (Cbfa1) showed that Cbfa1 is an essential transcription factor in osteoblast differentiation and bone formation. Furthermore, both in vitro and in vivo studies showed that Cbfa1 plays important roles in matrix production and mineralization. However, it remains to be clarified how Cbfa1 controls osteoblast differentiation, bone formation, and bone remodelling. To understand fully the physiological functions of Cbfa1, we generated transgenic mice that overexpressed C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
368
2
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(399 citation statements)
references
References 44 publications
(57 reference statements)
23
368
2
6
Order By: Relevance
“…Potential mechanisms may involve heightened expression of Runx2 in our TWIST-1 and DERMO-1 overexpressing MSC lines, whereas previous studies reported that high levels of Runx2 caused a reduction in the expression of target genes such as OCN, resulting in an inhibition of bone cell differentiation [47][48][49]. Alternatively, Twist-1 and Dermo-1 may be acting directly to inhibit the expression of genes such as OPN and BSP that contain putative of E-boxlike binding sites on their promoters (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…Potential mechanisms may involve heightened expression of Runx2 in our TWIST-1 and DERMO-1 overexpressing MSC lines, whereas previous studies reported that high levels of Runx2 caused a reduction in the expression of target genes such as OCN, resulting in an inhibition of bone cell differentiation [47][48][49]. Alternatively, Twist-1 and Dermo-1 may be acting directly to inhibit the expression of genes such as OPN and BSP that contain putative of E-boxlike binding sites on their promoters (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…Insufficient downregulation of RUNX1 due to the increased dose at a certain stage of megakaryocyte differentiation may result in disturbed regulation of cell proliferation and could eventually give rise to TAM, then leukemia. Consistent with this notion, Runx2 Tg mice which overexpress Runx2 also showed impaired differentiation of T-cell or bone development (Vaillant et al, 1999;Liu et al, 2001). On the other hand, another mechanism, a constitutive expression of RUNX1 that may be caused by an increased dose should be considered carefully, since RUNX1 is shown to be regulated in a cell-cycledependent manner (Bernardin-Fried et al, 2004).…”
Section: Discussionmentioning
confidence: 83%
“…In a recent in vivo study, Nagata et al 25 demonstrated that a large volume of PRP combined with autogenous bone graft decreased the expression of osteopontin. Because osteopontin is related to osteoblast function, 26,27 this seems to indicate that a large volume of PRP may have a cytotoxic effect on graft healing. A large volume of PRP may also form a clot that could restrict vascular flow inside the graft and decrease the number of bone cells.…”
Section: Discussionmentioning
confidence: 99%